The optimal oxytocin infusion rate for preventing uterine atony during cesarean delivery in elderly parturients with prior history of cesarean delivery - Wang, Li Ying; Wang, Jin; Dong, Jin Hua; Ping, Ze Peng; Chen, Xin Zhong; Wei, Chang Na (Frontiers in Pharmacology, 2023)
Background An estimate of 90% effective dose (ED90) of oxytocin infusion has already been proved effective in nonlaboring parturients. However, the requirements of oxytocin for elderly parturients with prior history of cesarean delivery may be higher. The aim of this study was to find the optimum oxytocin infusion rate for preventing uterine atony during cesarean delivery in elderly parturients with prior history of cesarean delivery. Method We performed a randomized, double-blinded study in 120 healthy elderly parturients with prior history of CD scheduled for elective CD under combined spinal-epidural anesthesia (CSE). Participants were treated with oxytocin infusion randomly at the rate of 0, 4, 8, 12, 16, or 20 IU h−1 after delivery of the infant. Following oxytocin administration, a blinded obstetrician evaluated the uterine tone (UT), verbally describing it with numerical scales (0-10; 0, no UT; 10, optimal UT) as either adequate or inadequate at the time intervals of 3 minutes, 6minutes, and 9 minutes. Maternal adverse effects, requirements for additional uterotonic agents, delivery- placental delivery (PD) time and estimated blood loss (EBL) were recorded. Results The 50% effective dose (ED50) and 90% effective dose (ED90) of oxytocin infusion were measured to be 14.6 IU h− 1 (95% confidence interval 12.0–18.4 IU h− 1) and 27.7 IU h− 1 (95% confidence interval 22.5–39.4 IU h− 1). The parturients in need of a rescue oxytocin dose and the Delivery-PD time decreased when the increment of infusion rate. Parturients receiving 0 IU h− 1 oxytocin at 3, 6 and 9 min got lower UT scores compared with 16 and 20 IU h− 1 oxytocin group (P<0.05, respectively). No significant among-group differences in the EBL and maternal adverse effects were observed. Conclusion An infusion rate of oxytocin at 14.57 IU h− 1 and 27.74 IU h− 1 will produce adequate uterine tone in 50% and 90% of elderly parturients with prior history of cesarean delivery respectively. 27.7 IU h− 1 oxytocin infusion is suggested to be the optimum dose for preventing uterine atony during cesarean delivery in elderly parturients with prior history of cesarean delivery.